Reaction Kinetics of an Industrial Front‐End Acetylene Hydrogenation Catalyst Using the Advanced TEMKIN Reactor. Issue 11 (13th July 2022) - Hock, Sebastian; Iser, Leonhard; Lucas, Martin; Rose, Marcus
Abstract: The front‐end process integration of the selective acetylene hydrogenation provides several advantages over the tail‐end option. But extensive knowledge of the process and reaction kinetics are required. This work combines the ideal conditions of the advanced TEMKIN reactor in a laboratory plant for gradient‐free kinetic analysis of eggshell catalyst under industrially relevant front‐end conditions. With this system an industrial state of the art Pd‐Ag/Al2 O3 eggshell catalyst is investigated and the temperature dependent data under various feed compositions including information on the formation of C4 ‐species are reported. Abstract : A laboratory plant with the advanced TEMKIN reactor for non‐destructive testing of eggshell catalysts under highly realistic front‐end conditions is presented. With this, the temperature and feed dependent catalytic data of an industrial state of the art Pd‐Ag/Al2 O3 catalyst is reported.